Pemberdayaan Perempuan Melalui UMKM Pada Ibu-Ibu Majelis Taklim Namirah - Muhammad As’ad; Zaman Zaini; Syamsiah Badruddin (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2018)
The economic burden that is so heavy is felt by most housewives as financial managers. Therefore, mothers must be able to manage their finances properly and also empower themselves by increasing income through Micro, Small and Medium Enterprises.Applying the right way of financial management, the housewife is expected to get the maximum benefits from the money she has at this time so that it can ultimately be beneficial for improving the welfare of life while increasing family income through MSMEs.Majelis Taklim/ MT Namirah is a member of the Majelis Taklim who live in Makassar City, South Sulawesi as the partner of this activity. Alternative problem solving is done by conducting public lectures for MT Ibu-ibu Namirah by the post graduate lecturer at the Institut Ilmu Sosial dan Manajemen Stiami, according to their competence, namely Family Development in household, Women's Participation in politics, and Management of Household Finances and Women's Empowerment in MSMEs. Some factors that support the implementation of community service activities by conducting public lectures are the amount of interest and enthusiasm of the mothers as participants in the activities so that the activities take place smoothly and in an orderly manner. While the limiting factor is the limited time for public lectures.This activity can increase the knowledge and understanding of MT Namirah ladies about financial management and types of businesses, knowing tips for dealing with obstacles in managing household finances and MT women’s businesses. Namirah, and get the knowledge and understanding of MT Namirah about the need for halal financial sources in financial management.